TOXICITY EFFECT OF COPPER ON THE SURVIVAL, BEHAVIOUR AND HISTOPATHOLOGICAL CHANGES IN THE LIVER, INTESTINE AND KIDNEY IN A FRESHWATER TELEOST, HETEROPNEUSTES FOSSILIS (BLOCH) - BAKSHI, NEENA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1991)
Effects of copper ions on the behaviour, tolerance and histopathological changes in liver, intestine and kidney of low and high concentrations, on H. fossilis have been studied. Varying concentrations from 20 to 200 ppm were used. Movement of fish, opercular movement increase with the higher concentration of copperions. Mortality occurs after 48 hrs at 100 ppm and higher concentrations. Histopathologically hepatic cells, mucous cells of intestine and tubular lining and glomeruli were ruptured at 175 ppm and higher concentrations.